Welfare indicators of Jersey heifers raised in semi-confinement and confinement systems with and without homeopathic supply (Research, Society and Development, 2024)
Ruminants, when raised in intensive systems and presented with variables that potentiate stress, can develop behavioral stereotypes. In addition, the diets present less bulky confinement compared to forage diets while cattle consume pasture. These dietary changes, or behavioral factors, can contribute to more confined behavior behavior and when animals use fewer behaviors or factors that can contribute to more reliable behavior behavior. Still, the amount of information on these situations is scarce, so the objective was to evaluate whether a study of inclusion of an animal, in the diet of non-inclusion of a history of animal behavior, can reduce the risk of abnormal behavior, considering two to reduce abnormal behavior patterns rearing system (confinement and semi-confinement) and pre- and post-feeding exams. Fourteen were used in the Face of this, the Jersey breed with 12 months of age, fortresses in two groups of seven each. The study lasted 60 days, with the first 30 days in a semi-confinement system (Jersey with access to pasture) and the last 30 days in confinement. By an observer, three times a week (Monday, Wednesday and Friday) behavioral data were collected before and after the afternoon feeding. At the end of each stage (days 28, 29 and 30; and days 58, 59 and 60), two or three observers collected heifer behavior three times a day, with each observation lasting 50 minutes. Among the results obtained, vocalization was 66% less likely to occur for the treatment group. The influence system to curl the tongue, being this abnormal behavior more present in the confined system during the experimental period. The system also had under rumination, presenting 77% less chance of occurrence for confined animals. Other behaviors (on sandbanks and licking other animals) were also influenced by the breeding system. With the exception of tongue curl, all other animals kept from the moment, that is, effect before and after feeding. From an observation of the influence of the semi-confined system on the occurrence of natural behavior and as a result of the restriction, suggesting that this system is protected by greater conditions of less comfort, it presents stereotypic results.